DEMOKRASI KEBEBASAN BERPENDAPAT: DEMOKRASI KEBEBASAN BERPENDAPAT - Natasya Putri Wiguna; Vitria Vitria Anggraini; Khairunnisa Dwi Rachmasari (Jurnal Komunikasi Dialogis, 2026)
Abstract - Freedom of expression is a fundamental human right and a pillar of democracy, but the rapid expansion of social media in Indonesia has created tensions between digital participation and regulatory control. The Electronic Information and Transactions Law (UU ITE) has been criticized for its open-ended provisions that potentially limit critical political speech. This study examines the representation of political opinion and freedom of expression on Indonesian social media, focusing on the impact of the ITE Law on digital democracy. Using quantitative content analysis, the study analyzed 15 posts from three influential accounts—@kemkomdigi (government), @andovidalopez (political influencer), and @kumparan (news media)—on platforms X and Instagram during September–October 2024, coinciding with student demonstrations against the revision of the TNI Law, the increase in VAT, and the enforcement of the ITE Law. The findings indicate that criticism of government policies dominated (40%), followed by political support (27%), discussions of freedom of expression (20%), and sarcasm (13%). Instagram featured more visual, support-oriented content, while X was dominated by critical text-based posts. Critical and sarcastic content received approximately twice as much engagement (likes and retweets) as other themes. The ITE Law contributed to a chilling effect, reducing oppositional expression after the demonstrations. Influencer accounts reinforced polarization through high engagement with critical content. This study recommends revising the ITE Law to reduce ambiguity, improve digital literacy, and monitor influential accounts to promote inclusive democratic discourse.